Analisis Keanekaragaman Tumbuhan Famili Araceae di Taman Wisata Alam Suranadi, Lombok Barat - Sri Wahyuni Budi Lestari; Baiq Muli Harisanti; Septiana Dwi Utami (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The Araceae family (taro) is a group of understory plants that have high diversity and play an important role ecologically and economically, but some of its species are still less well known by the public. This study aims to identify the types of plants of the Araceae family and analyze their diversity levels in the Suranadi Nature Tourism Park (TWA). The study used a descriptive exploratory method with a quadrat transect technique at three observation stations. Each station consisted of two plots measuring 5 × 5 m, resulting in six observation plots. The results of the study found 11 species of Araceae belonging to 8 genera with a total of 118 individuals. The genus with the largest number of species is Syngonium (3 species), followed by Dieffenbachia (2 species), while the other genera each consist of 1 species. The Shannon-Wiener diversity index value ranged from 0.772–1.491 with a low to moderate category. Environmental conditions of 26–28°C, 55–75% humidity, and a soil pH of 5.5–6.0 indicate that the Suranadi Natural Park (TWA) offers suitable habitat conditions for the growth of Araceae. The results of this study indicate that the Suranadi Natural Park has a relatively high diversity of Araceae and can serve as a source of information for conservation, education, and area management.